Associação genética entre características produtivas, de carcaça e idade ao primeiro parto na avaliação genética da raça nelore - Menezes, Flávio Luiz de (2022)
ABSTRACT: In genetic evaluation animal programs, commonly over time, new selective criteria related to the expression of carcass, reproductive and economic performance are added. In this sense, traits related to productive performance are easy to measure and with good responses to selection. Currently, sexual precocity is a criterion widely used as essencial to intensification in production systems, however, for most of these traits, low heritability estimates are observed and, therefore, with lower responses to selection. Thus, more accurate methodologies are needed to identify superior genotypes. Traits related to carcass evaluation are presented with moderate to high heritability estimates, and selection for them results in increased carcass yield. Thus, in selective indices that combine a set of traits related to such criteria, it is important to know the genetic interrelationships between them, in order to maximize the expected genetic gain. The objective this study was to evaluate the genetic associations between selection criteria for sexual precocity traits with productive performance and carcass traits in cattle.